PENGEMBANGAN DIGITAL BOOK BERBASIS ANDROID UNTUK MENSTIMULUS PSIKOMOTORIK SISWA - Syafruddin Syafruddin (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2019)
This study aims to: (1) produce an android-based digital book application to concretize students' motoric understanding on the Fiqh subject matter in waqf (endowment) lesson, and (2) find out the extent of the appropriateness (quality) of the application that have been developed. The research is Research and Development (R & D) using the model of Alessi and Trollip which is adjusted based on the needs of the researcher. The development procedure consists of three stages (a) planning, (b) design, and (c) development which includes standards, ongoing evaluation, and project management. This research resulted in: (1) Android-based digital book application and guidebook for user, and (2) have quality based on a feasibility trial through alpha test and beta test. Alpha test was assessed by two material experts with a mean score of 3.40 (very feasible), and 3.45 by media experts (very feasible). Beta Test is carried out in small group of 6 students with a total score of 3.53 and a very feasible category. The increase occurred when a large group trial of 30 students of MAN 1 Pidie Class X IPA with a total score 3.67 was categorized as very feasible. Based on the feasibility trial, it is possible for an Android-based digital book application to be able to stimulate the psychomotor component of students for the learning of Fiqh subject in waqf (endowment) lesson.